ANIMALS, TALE TYPES, AND BELIEF NARRATIVES IN ARGENTINEAN FOLKLORE. - Palleiro, María Inés (Folklore (14060957), 2019)
Tales regarding transformations of animals, expressing social beliefs related to the relationship between humans, animals, and supernatural beings, are spread all over the world. This paper deals with the intertwining of ritual discourse, animal tales, and other folk narrative genres, all of which express the differential identities of local groups. The aim is to discuss the relevance of belief narratives in an Argentinean catalogue of tale types, whose first volume includes animal tales. Following the models of Monika Kropej Telban (2015) and Camiño Noia Campos (2010), who include in their indexes of Slovenian and Galician folktales textual examples of each tale type, my purpose is to show the local transformation of universal tale types in the catalogue of Argentinean folktales. I analyze textual examples of this blend between tale types and belief narratives with the aim of proposing a classification of Argentinean folktales not only into tale types but also into narrative matrices, which share thematic, structural, and stylistic features. The goal of this folk narrative catalogue is to show how local beliefs transform universal narrative patterns into expressions of vernacular identities. To contextualize this approach concentrating on the interweaving of animal tales and belief narratives, I also present a diachronic overview of Argentinean folk narrative collections focused on animal tales, from 1921 up to the present day.